2016
DOI: 10.1007/s13202-015-0224-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of flow units using methods of Testerman statistical zonation, flow zone index, and cluster analysis in Tabnaak gas field

Abstract: The relation between porosity and permeability parameters in carbonated rocks is complicated and indistinct. Flow units are defined with aim of better understanding reservoir unit flow behavior and relation between porosity and permeability. Flow units reflect a group of rocks with same geological and physical properties which affect fluid flow, but they do not necessarily coincide with boundary of facies. In each flow unit homogeneity of data is preserved and this homogeneity fades in the boundaries. Here, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The cumulative percentage of flow vs. storage capacities were plotted to obtain a curve. The slope or the points of the inflexions were then interpreted preliminarily to represent various FU intervals, whether they are efficiency zones, baffle or barrier units (Chopra et al 1987;Newsham and Rushing 2001;Gomes et al 2008;Mahjour et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The cumulative percentage of flow vs. storage capacities were plotted to obtain a curve. The slope or the points of the inflexions were then interpreted preliminarily to represent various FU intervals, whether they are efficiency zones, baffle or barrier units (Chopra et al 1987;Newsham and Rushing 2001;Gomes et al 2008;Mahjour et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Identification of permeability is of major importance to identify productive flow zones in a geothermal aquifer (Mahjour et al 2016). Permeability is a rock property that is directly linked to pore size and effective porosity and varies widely in heterogeneous carbonate deposits from < 0.01 millidarcy (mD) to well over 1 Darcy (Lucia 2007).…”
Section: Permeabilitymentioning
confidence: 99%
“…This technique mostly helps to divide a ''pile'' of information into the meaningful groups based on the group's similarity. These obtained groups are internally homogeneous and externally heterogeneous (Mahjour et al, 2016;Stinco et al, 2001). The base of clustering method is the distance between two data objects in one matrix to measure the similarity of data.…”
Section: Identification Of Flow Units Using Hca Methodsmentioning
confidence: 99%
“…Aminian et al (2003) delivered a neural network technique to determine flow unit types and predict the petrophysical parameters in the reservoir. Mahjour et al (2016), made a comparison of different methods to identify flow units in the Tabnak gas field in southern Iran. They concluded that Hierarchical Cluster Analysis (HCA) is more efficient than the other methods used for the general assessment of flow units in field scale.…”
Section: Introductionmentioning
confidence: 99%